2007
DOI: 10.1021/ja076721g
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Mechanism for the Chemoselective Hydrogenation of Substituted Nitroaromatics with Nanoparticles of Gold on TiO2 Catalysts:  A Cooperative Effect between Gold and the Support

Abstract: Nanoparticles of gold on TiO2 are highly chemoselective for the reduction of substituted nitroaromatics, such as nitrostyrene. By combining kinetics and in situ IR spectroscopy, it has been found that there is a preferential adsorption of the reactant on the catalyst through the nitro group. IR studies of nitrobenzene, styrene, and nitrostyrene adsorption, together with quantum chemical calculations, show that the nitro and the olefinic groups adsorb weakly on the Au(111) and Au(001) surfaces, and that althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
374
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 483 publications
(391 citation statements)
references
References 21 publications
17
374
0
Order By: Relevance
“…During transition to uncharged Au 12 0 (3D) structures that contain flat elements (planes) and structural defects (corners and edges), the Q(H 2 ) increases up to 78 kJ/mol. The obtained results confirmed the existing hypotheses on the positive impact of cluster defects to the activation of H 2 [13,30,[32][33][34][35] and are in agreement with explanation of NiO/ Au synergy (II).…”
Section: The Nature Of Au Activation In Nio/au Clusterssupporting
confidence: 90%
See 1 more Smart Citation
“…During transition to uncharged Au 12 0 (3D) structures that contain flat elements (planes) and structural defects (corners and edges), the Q(H 2 ) increases up to 78 kJ/mol. The obtained results confirmed the existing hypotheses on the positive impact of cluster defects to the activation of H 2 [13,30,[32][33][34][35] and are in agreement with explanation of NiO/ Au synergy (II).…”
Section: The Nature Of Au Activation In Nio/au Clusterssupporting
confidence: 90%
“…The better hydrogenation activity of 2.5 nm gold particles can be explained if the chemisorption of H 2 is dependent on gold particle size. Our recent research on the TOF of Au particles of different sizes (2-30 nm) in hydrogenation of ethynylbenzene [13] and studies by Bus [30,31], Serna [32], Boronat [33], and Jia [28] have proved the positive influence of small gold clusters on hydrogenation rate. It was concluded that H 2 is dissociatively adsorbed only at the corners and edges of the supported gold particles [34,35].…”
Section: Resultsmentioning
confidence: 96%
“…With decreasing particle size, increasing amounts of hydrogen are chemisorbed and an increasing fraction is adsorbed strongly. Thus it can be concluded, that the chemisorption is limited to low coordinated corner and edge atoms, which was recently confirmed by theory (50).…”
Section: Interaction Of Gold and Hydrogensupporting
confidence: 67%
“…Gold catalyzes various hydrogenation reactions such as the hydrogenation of alkenes (3)(4)(5)(6)(7)(8)(9)(10)(11)(12), alkadiens (13)(14)(15)(16)(17)(18) alkynes (13,(19)(20)(21)(22)(23)(24)(25), , -unsaturated carbonyl compounds and nitro compounds (47)(48)(49)(50)(51)(52)(53). In contrast to traditional hydrogenation catalysts such as platinum, palladium or ruthenium, which require modification, it often shows remarkable selectivities when multiple functional groups are present.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the relative instability and the difficulty for the formation of Au-hydrides, Au NPs-catalyzed reduction protocols are more controllable and selective relative to the analogous Pd or Pt-catalyzed processes; the facile accumulation of Pd or Pt-hydrides on the catalyst's surface often leads to side reactions (e.g., dehalogenation or overeduction pathways). 7 While much effort has been devoted to Au-catalyzed reduction of carbonyl and nitro compounds, there are only a few examples regarding the reduction of π systems. Cao and co-workers have shown that Au NPs supported on high surface area titania (HAS-TiO 2 ) catalyze the chemoselective reduction of quinolines into 1,2,3,4-tetrahydroquinolines using H 2 .…”
Section: Introductionmentioning
confidence: 99%